Signals for new spin-1 resonances in electroweak gauge boson pair production at the LHC - Alves, A. [UNESP]; Eboli, O. J. P.; Netto, D. Goncalves; Gonzalez-Garcia, M. C.; Mizukoshi, J. K. (Amer Physical Soc, 2009)
The mechanism of electroweak symmetry breaking ( EWSB) will be directly scrutinized soon at the CERN Large Hadron Collider. We analyze the LHC potential to look for new vector bosons associated with the EWSB sector, presenting a possible model independent approach to search for these new spin-1 resonances. We show that the analyses of the processes pp -> l(+)l(1-)E(T), l +/- jjE(T), l(1 +/-)l(+)l(-)E(T), l(+/-)jjE(T), and l(+)l(-) jj (with l, l' = e or mu and j = jet) have a large reach at the LHC and can lead to the discovery or exclusion of many EWSB scenarios such as Higgsless models.